Management of Sports Facilities and Infrastructure DISPORA Salatiga City in Facing the Digital Era in 2024 - Fatma, Maranthika Fony Zul; Nurrachmad, Limpad (Universitas Majalengka, 2025)
The rapid development of digital technology has affected many aspects of life, including sports. Dispora Salatiga City, as the institution responsible for managing sports facilities and infrastructure, is certainly faced with challenges and obstacles in adapting to the digital era. This study aims to analyze the optimization of sports facilities and infrastructure management in Salatiga City in facing the digital era, focusing on digital implementation. This research method uses a qualitative approach. Data was collected through direct observation, in-depth interviews with the Dispora, and documentation. The data obtained was analyzed qualitatively through the following stages: data collection, data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation of sources and data. The results showed that Salatiga City Youth and Sports Office has started to implement digital technology into four management functions: planning, organizing, implementing, and supervising. However, implementing digitalization still faces several obstacles, including limited technology-savvy human resources, lack of digital infrastructure, and suboptimal budget allocation. To improve the quality of management in the digital era, the Salatiga City Youth and Sports Office is advised to strengthen technology training for staff, optimize collaboration with the private sector, and take advantage of central government programs related to the digitization of public services. With these steps, it is expected that sports facilities and infrastructure can be managed more transparently, easily accessible, and support the advancement of sports in Salatiga City.